The modulation of PI3K/Akt pathway by 3β hydroxylup‐12‐en‐28‐oic acid isolated from Thymus linearis induces cell death in HCT‐116 cells - Bashir, Rohina; Ahmad Zargar, Ovais; Hamid Dar, Abid; Yedukondalu, Nalli; Parvaiz, Qazi; Hamid, Rabia (Chemical biology & drug design, 2022)
The presence of intricate carbon skeletons in natural compounds enhances their bioactivity spectrum with unique modes of action at several targets in various dreadful diseases like cancer. The present study was designed to purify the molecules from Thymus linearis and elucidate their antiproliferative activity. The compounds were isolated from the active methanolic extract of Thymus linearis through column chromatography and characterized by various spectroscopic techniques. Antiproliferative activity of isolated compounds was evaluated using MTT assay on cancer and normal cell lines. Mechanism of cell death was elucidated using flow cytometric, microscopic, and Western blot analysis. Four compounds, Sitosterol, Chrysin, 3β‐hydroxylup‐12‐en‐28‐oic acid (3BH), and β‐Sitosterol glycoside, were isolated. Among these, 3BH was most potent antiproliferative agent across all cell lines under study, HCT‐116 being the most affected one. 3BH was demonstrated to downregulate PI3Ksubunits (p110α and p85α), downstream pAktSer473 and prompted G1 phase cell cycle arrest. The cell cycle CDK inhibitor p27 and p21 were upregulated with simultaneous downregulation of cyclin D1 and cyclin E in HCT‐116 cells. This was accompanied by apoptosis, as depicted by decrease in Bcl‐2/Bax ratio, with increase in active caspases‐3 and caspase‐9, cleavage of PARP‐1, the generation of reactive oxygen species (ROS), and the loss of mitochondrial membrane potential. The findings established that 3BH induced cell death in HCT‐116 cells by modulating PI3K/Akt signaling axis, impeding cell cycle, and instigating apoptosis. 3β‐hydroxylup‐12‐en‐28‐oic acid isolated from Thymus linearis targets P110α in HCT‐116 and elicits apoptotic pathway.